3D Resistivity Modeling of Aquifers Based on Geoelectrical Data in Parungmulya Village, Karawang, West Java - Az Hafiz Syach Putra Nugroho; Muhammad Faisal; Ananda Nur Fitria; Riane Agissa Putri; Devi Apriliani; Rahma Oktavia Helena (Department of Physics, Faculty of Science and Technology, UIN Syarif Hidayatullah Jakarta, 2025)
Parungmulya Village, Karawang Regency, West Java, faces challenges in accessing clean water. This study aims to identify groundwater potential in the area using the resistivity geoelectric method. Measurements were conducted along six survey lines using the Schlumberger configuration to analyze subsurface layer characteristics and aquifer potential. The results indicate that a sandstone layer with high porosity and permeability has the potential to serve as a groundwater source for the local community. The resistivity values for this sandstone range from 306 to 2675 Ohm.m, with a maximum volume of 7,178.1 m³. This layer demonstrates a significant capacity for storing and transmitting groundwater. Additionally, a tuffaceous sandstone layer also exhibits aquifer potential, with resistivity values ranging from 408 to 1488 Ohm.m and a total volume of 28,892 m³. The findings of this study are expected to serve as a foundation for groundwater exploration planning to mitigate the water shortage problem in Parungmulya Village.